1986
DOI: 10.1007/bf00453767
|View full text |Cite
|
Sign up to set email alerts
|

Ca++ activity in the endolymphatic space

Abstract: We measured Ca++ activity in the different parts of the endolymphatic space by using a double-barrelled electrode with calcium liquid ionic exchanger. In the region of the endolymphatic sac, Ca++ activity (4.7 X 10(-4) M) was much higher than in the cochlear duct (2.7 X 10(-5) M) and semicircular canal (2.6 X 10(-4) M). These findings suggest that Ca++ may also have a significant role in abnormal states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Their functional role has not been clarified. Putative functions include maintenance of homeostasis (10,11) and pressure (12) of the inner ear, phagocytosis of debris (13), and immunologic functions (14,15). ELSTs can cause hearing loss, tinnitus, vertigo, and facial nerve paresis.…”
Section: Introductionmentioning
confidence: 99%
“…Their functional role has not been clarified. Putative functions include maintenance of homeostasis (10,11) and pressure (12) of the inner ear, phagocytosis of debris (13), and immunologic functions (14,15). ELSTs can cause hearing loss, tinnitus, vertigo, and facial nerve paresis.…”
Section: Introductionmentioning
confidence: 99%
“…In hearing organs, the Ca 2ϩ concentration has been estimated to be as low as 30 M in mammals (5)(6)(7)(8) and 65 M in reptiles (9). In vestibular organs, the Ca 2ϩ concentration is higher than in the cochlea: it measures Ϸ100 M in the guinea pig's sacculus and utriculus (6) and Ϸ250 M in the guinea pig's semicircular canal (7,8) and the bullfrog's sacculus (10). Tight junctions between epithelial cells maintain the distinct ionic compositions of endolymph and perilymph (reviewed in ref.…”
mentioning
confidence: 99%
“…11,26, 28, 29], Alterations in the TM after glycerol administration are transient, which may be due to the fact that this structure is highly sensi tive to changes in the ionic environment [24,25,27,28]. The ionic equilibrium is disturbed in experimental hy drops [30,31] and after glycerol treatment in the nonhydropic and short-term-hydropic specimens [4], The reorganization of the CD 15 epitope of the TM in higher turns of the cochlea after glycerol administration were paralleled by decreased Ca2+ in the endolymph measured in the third turn [4]. As shown by Hakomori [16] the strong adhesion between Lex (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…CD 15) molecules de pends on the presence of high Ca2+. The endolymphatic Ca2+ concentration is in the 20-\iM (first turn) and 30-pM (third turn) range [4,[30][31][32] and it has been shown that the concentration decreases during glycerol administra tion in non-hydropic and hydropic animals in the third turn [4], It is therefore possible to suggest that glycerol transiently disturbs the Donan equilibrium of the TM [25] and causes the Ca2+ gradient between the endolymph and the TM. This may be a way to increase the Ca content in the TM transiently and may explain its abundant aggre gation and reorganization of the CD 15 epitope in higher turns.…”
Section: Discussionmentioning
confidence: 99%